Destructive Factors on Parishan Lake Ecosystem, Iran - Azodi, Toba Amir; Arbabi, Azadeh (International Journal of Bio-resource and Stress Management, 2011)
Kazerun covers one of the most precious and beautiful natural regions of Fars Province. Parishan lake, also known as Famour pond is on the east of Kazerun. The scenery during spring and fall was very attractive, and the green and flower fields around the lake and presence of wild birds made a very astonishing natural resort. At present, the lake has almost lost its natural ornaments because of over-exploitation of its resources and unusual human intervention in and around. In this article, a brief study of the animals and plants specifications of Parishan Lake before fire and also the important factors responsible for destruction are presented. The Methodology includes documentary as well as field study.